2020
DOI: 10.4018/978-1-5225-9611-0.ch012
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biometric Image Enhancement Approach With the Hybridization of Undecimated Wavelet Transform and Deep Autoencoder

Abstract: For a long time, image enhancement techniques have been widely used to improve the image quality in many image processing applications. Recently, deep learning models have been applied to image enhancement problems with great success. In the domain of biometric, fingerprint and face play a vital role to authenticate a person in the right way. Hence, the enhancement of these images significantly improves the recognition rate. In this chapter, undecimated wavelet transform (UDWT) and deep autoencoder are hydridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…While constructing a deep autoencoder, each layer receives its input from previous layer. In particularly, the autoencoder is trained to convert the raw input into some latent or more abstract representation and the output is reconstructed from that compressed representation [25][26][27][28][29]. The encoder receives the raw data as input I(x) ∈ R d and maps into a latent representation H(x) ∈ R � with the function as, Here, sigmoid is used as the learning function.…”
Section: Deep Autoencodermentioning
confidence: 99%
“…While constructing a deep autoencoder, each layer receives its input from previous layer. In particularly, the autoencoder is trained to convert the raw input into some latent or more abstract representation and the output is reconstructed from that compressed representation [25][26][27][28][29]. The encoder receives the raw data as input I(x) ∈ R d and maps into a latent representation H(x) ∈ R � with the function as, Here, sigmoid is used as the learning function.…”
Section: Deep Autoencodermentioning
confidence: 99%
“…10,11 Recent studies have also demonstrated that when dealing with signals, their transformation into images could provide competitive results in supervised setups. [12][13][14] In these works, the authors show that encoding time series to images can help to emphasize, capture, or condense local patterns that would otherwise be spread over time. In the literature, we identified four promising encoding algorithms: the Gramian Angular Field, the Markov Transition Field, 15 the recurrence plot, 16 and grey scale encoding.…”
Section: Introductionmentioning
confidence: 99%